2022
DOI: 10.3390/nu14071525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Hydroxytyrosol Administration on Body Weight, Fat Mass and Urine Metabolomics: A Randomized Double-Blind Prospective Human Study

Abstract: Hydroxytyrosol (HT) is a natural antioxidant found in olive products and characterized by well-documented beneficial effects on human health. Several research studies are ongoing that aim to investigate its potency and molecular mechanism of action. The present study aimed to investigate the potential effect of HT on human obesity through a randomized double-blind prospective design. HT in two different doses (15 and 5 mg/day) and a placebo capsule was administered to 29 women with overweight/obesity for six m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Repeated dose oral toxicity studies have highlighted a potential effect of olive extract and pure HT in relation to decreases in body weights and/or body weight gain in rodents [60] , [61] , without alteration on food consumption or any other toxicologically relevant findings. Reduction in body weight gain is one of the benefits of olive oil in the context of Mediterranean diet and has been reported in a clinical trial [36] . Several mechanisms have been proposed to explain the weight loss after polyphenols supplementation, such as increased lipolysis and activated β-oxidation through downregulation of the expression of peroxisome proliferator-activated receptor (PPAR)-α and PPAR-γ and by activation of 5’AMP-activated protein kinase and lipase; a prebiotic effect for gut microbiota [89] , [90] , [91] ; inducing satiety; an inhibition of adipocyte differentiation; and a promotion of adipocyte apoptosis [92] .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Repeated dose oral toxicity studies have highlighted a potential effect of olive extract and pure HT in relation to decreases in body weights and/or body weight gain in rodents [60] , [61] , without alteration on food consumption or any other toxicologically relevant findings. Reduction in body weight gain is one of the benefits of olive oil in the context of Mediterranean diet and has been reported in a clinical trial [36] . Several mechanisms have been proposed to explain the weight loss after polyphenols supplementation, such as increased lipolysis and activated β-oxidation through downregulation of the expression of peroxisome proliferator-activated receptor (PPAR)-α and PPAR-γ and by activation of 5’AMP-activated protein kinase and lipase; a prebiotic effect for gut microbiota [89] , [90] , [91] ; inducing satiety; an inhibition of adipocyte differentiation; and a promotion of adipocyte apoptosis [92] .…”
Section: Discussionmentioning
confidence: 92%
“…Finally, in a very recent prospective, randomized, double-blinded and placebo-controlled study, evaluating the effects of long term (6 months) of oral supplementation with 15 and 5 mg/day of HT among 29 overweight/obese women, no adverse events were reported by the subjects. The product was considered safe and well-tolerated by the authors [36] . Note that in this study, statistically significant weight and visceral fat mass loss (%weight loss: p = 0.012, %visceral fat loss: p = 0.006) were observed in the group receiving the maximum HT dose as compared to the placebo group after 4 weeks of the intervention, with attenuation of these findings at 12 and 24 weeks [36] .…”
Section: Discussion and Safety Reviewmentioning
confidence: 93%
See 2 more Smart Citations
“…Patients were randomly assigned to 2 capsules of an oral supplement containing 2.5 mg HT and 412.5 mg olive oil extracts po twice daily (Olivomed, Intermed) or placebo (OOHT or Placebo) and after 1‐month treatment were crossed over to the alternate treatment (Placebo or OOHT) for 1 month (Figure 1). We selected a dose of 10 mg/day for HT, as data from a recent study showed that 15 mg ΗΤ was effective for weight loss and visceral fat mass loss, whereas the dose of 5 mg had no effect, implying the need of increased HT dosage to succeed a sufficient antioxidant and anti‐ inflammatory effect 17 …”
Section: Methodsmentioning
confidence: 99%